HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN KETERAMPILAN KOMUNIKASI INTERPERSONAL SISWA DI SMP N 1 TIGO NAGARI - Fiki Kurnia; Afrinaldi (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the existence of students who have difficulty in developing their emotional intelligence such as lack of self-awareness so they often think they are right and don't care about those around them, students are less able to control their emotions in solving problems because there is no sense of caring for others and only prioritizes emotions, and students are less able to manage themselves and their emotions so that many students behave rudely both with peers and with teachers at school, there are students who have difficulty in developing their interpersonal communication skills such as mocking each other and not appreciating teachers such as saying disrespectful so that it hinders learning activities. The purpose of this study is to find and determine the relationship between emotional intelligence and students' interpersonal communication skills. This research belongs to the quantitative regression research. The population in this study amounted to 160 students. The sample in this study amounted to 40 students taken using the proportional stratified random sampling technique. Collecting data using a questionnaire method with a Likert scale. Test the hypothesis using the Product Moment correlation test with the help of SPSS 16. Based on the results of the F test, the calculated F price is 20.23 with a significance level of 0.102, while the F table at a 95% confidence level (0.05) in this test is carried out with a 95% confidence level. (0.05), namely: df1 = 2 – 1 = 1 and at df2 = 40 – 1 = 39 where the F value is calculated as large from the F table (20.23 > 4.09) with a significance level below 0.05 (0.102 < 0, 05). So, it can be concluded that the interpersonal communication variable (X) has a significant effect on learning achievement (Y). then the coefficient of determination value is 5.1%. Based on this value, it can be interpreted that the variance of adolescent learning achievement variables is influenced by 5.1% by interpersonal communication and 94.9% is influenced by other factors. Keywords: emotional intelligence, interpersonal communication